The Relationship of Simantri Management Implementation with Income Level of Farmers In Bali - A. R, Tetsuya; Suparta, I N.; Budiartha, I W. (Jurnal Peternakan Tropika, 2018)
Integrated agricultural system is one of the leading activities of the Bali Provincial Government in an effort to increase income and poverty alleviation in Bali. However, until now the implementation of Simantri has not been able to increase the member's income optimally. This study aims to determine the relationship of Simantri management implementation with income level of farmers in Bali. The study was conducted in eight districts spread in Bali, lasting for 3 months from April to July 2018. The selection of research sites using purposive method and the determination of samples using Stratified Purposive Sampling method. Respondents from this study amounted to 45 farmers members of Gapoktan Simantri. The analysis used is qualitative descriptive analysis and Spearman level correlation test. The results of this study indicate that the implementation of Simantri management in Bali Province included in the medium category. Increase in farmer income is included in the low category. Relation between the implementation of Simantri management with income level of Farmer who have followed the Simantri program in Bali Province has obivious significant (P<0.01). Suggestions that can be delivered are Farmers members of Gapoktan Simantri should apply livestock business units, food crops and waste treatment with more leverage, in order to reduce the production cost of Simantri managed to increase revenue. Keywords: Simantri, application, revenue, management